IMPLEMENTASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA DALAM PENYEDIAAN RUMAH LAYAK HUNI DI DESA TOLOK SATU KECAMATAN TOMPASO KABUPATEN MINAHASA - DESYRA, TENDEAN ELYSA; DENGO, SALMIN; LONDA, VERY (Sam Ratulangi University, 2021)
This study aims to determine the implementation of the self-help housing stimulant program inthe provision of livable houses in Tolok Satu Village, Tompaso District, Minahasa Regency.This study uses a descriptive qualitative approach by describing the data obtained from the resultsof research on the implementation of self-help housing stimulant assistance programs in the provision oflivable houses. The types of data used in this study are primary data and secondary data. Data wascollected by means of observation, interviews, documentation, and data analysis techniques consisting ofdata reduction, data presentation, and drawing conclusions. The theory used in this study consists of sixaspects: policy standards and objectives, resources, inter-organizational relations, characteristics ofimplementing agents, social, political and economic conditions as well as the disposition of theimplementor.The results of this study indicate that the implementation of the self-help housing stimulantprogram in providing decent housing in Tolok Satu Village, Tompaso District, Minahasa Regency has notrun optimally. Viewed from the aspect of the standard target recipients, the program has not gone well, therecruitment of beneficiaries has not been realized entirely because of the unpreparedness of thecommunity to receive this assistance. the two sources of funds from this program were not sufficient, thethree problems of socialization carried out by TFL as field facilitators only carried out socialization at thebeginning of the introduction of the program and did not re-socialize it to the recipient community so thatpeople did not understand the mechanism of this BSPS program, the four dispositions or attitudes TFLimplementors, field facilitators, do not yet have firmness in providing understanding to the recipientcommunity about the BSPS program, it must be carried out in predetermined groups, but the reality on theground is that the community only builds their own houses.Keywords: Implementation, Assistance Program, BSPS, Decent Homes